Interactions between Obsessional Symptoms and Interpersonal Ambivalences in Psychodynamic Therapy: An Empirical Case Study - Cornelis, Shana; Desmet, Mattias; Van Nieuwenhove, Kimberly L. H. D.; Meganck, Reitske; Willemsen, Jochem; Inslegers, Ruth; Feyaerts, Jasper (Frontiers in Psychology, 2017)
Background: The classical symptom specificity hypothesis (Blatt, 1974) links obsessional symptoms to autonomous interpersonal behavior. Inconsistent findings from cross-sectional group studies on symptom specificity have previously been associated with several conceptual and methodological limitations intrinsic to nomothetic research. Previous empirical case research reported ambivalences between autonomous and dependent interpersonal behavior in obsessional pathology. Aim and Method: The present ‘theory-building’ case study specifically aims at further refinement of the classical symptom specificity hypothesis by testing specific operationalizations within an empirical single case design. Consensual Qualitative Research for Case studies is used to quantitatively and qualitatively describe the longitudinal, clinical interplay between obsessional symptoms and interpersonal dynamics throughout the process of a psychodynamic therapy. Interpersonal functioning is assessed by means of the Core Conflictual Relationship Theme method. The classical symptom specificity hypothesis is contrasted to an alternative hypothesis of interpersonal ambivalences as determinants of obsessional symptoms. Results: Close associations between obsessions and interpersonal dynamics are observed. Findings predominantly affirm the ambivalence hypothesis rather than the classical symptom specificity hypothesis. Psychodynamic interventions focusing on interpersonal conflicts are related to symptomatic changes. Conceptual and methodological considerations, limitations and future research indications are discussed.